Penentuan Nilsi Opsi Saham Karyawan (OSK) dengan Memperhitungkan Efek Dilusi dengan Menggunakan Metode Black-Scholes - Annisa Fitri; Suherman Suherman (Journal of Mathematics UNP, 2020)
Abstract — This research will discuss how to determine the value of Employee Stock Options (ESO), in calculating it has a different way from other options. Dilution effects that causes a decrease in stock price returns that will be taken into account. This research is based on relevant theory and case examples will be simulated using computer software. The movement of stoks price will be modeled by the Black-Scholes method. The results of this study will get the ESO value and also see some influence of parameters. The influence of the parameters of interest rates (r) and volatility ( ) has a value directly proportional to the value of ESO. While the strike price (K), the rate of employees leaving the company ( ) and the length of waiting period (v) is inversely proportional to the value of ESO. Keywords —employee stocks options, dillution effect, black-scholes model.